Sectoral impact of fiscal policy in Malaysia - Law, Chee Hong (Penerbit Universiti Kebangsaan Malaysia, 2016)
The present study examines the responses of sectoral gross domestic product to different types of government revenue and total government expenditure. The findings are useful to determine the effectiveness of fiscal policy in different economic sectors, which were ignored by previous studies. This study involves six-variable vector autoregressions with Cholesky decompositions. The results indicate that the sectoral output, especially the output in the agricultural-related sector, is sensitive to government revenue. Additionally, a standard deviation of different government revenue shock is found to have a positive effect on sectoral output in most cases. This implies that a positive economic environment causes government revenue and economic output to increase. A rise in government income creates the expectation that government expenditure and investment will increase in the future. On the other hand, the sensitivity to government expenditure is not frequently found and their impacts are mainly positive. This is in line with economic theory. Finally, the analysis of variance decompositions shows that greater portions of the sectoral output are explained by government revenues.